2019
DOI: 10.1073/pnas.1914633116
|View full text |Cite
|
Sign up to set email alerts
|

Functional genetic validation of key genes conferring insecticide resistance in the major African malaria vector, Anopheles gambiae

Abstract: This PDF file includes: 640 Supplementary text: Cyp6 expression analysis using the ΔΔCt method 641 Figs. S1 to S4 642 Tables S1 and S2 643 29 Supplementary Text 644 Cyp6 expression analysis using the ΔΔCt method 645 Threshold cycle (Ct) values were corrected for primer efficiency applying the formula Corrected 646 Ct = Ct (Logx / Log2), where x = 2 if efficiency is >100% and x = 1+Efficiency if efficiency is 647 <100%. 648 Ct values obtained for target genes were normalised against those of the housekeeping ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 47 publications
1
85
1
Order By: Relevance
“…Likewise, high GSTs activity was reported to be associated with insect resistance to DDT and pyrethroids [59,69]. The following candidate genes used in this study (CYP6M2, CYP6P3 [70][71][72], CYP6Z2 [73], CYP4G16, CYP4G17 [19,74,75] and CYP9K1) have been reported to be involved in pyrethroid resistance in An. gambiae in Africa [76].…”
Section: Discussionmentioning
confidence: 70%
“…Likewise, high GSTs activity was reported to be associated with insect resistance to DDT and pyrethroids [59,69]. The following candidate genes used in this study (CYP6M2, CYP6P3 [70][71][72], CYP6Z2 [73], CYP4G16, CYP4G17 [19,74,75] and CYP9K1) have been reported to be involved in pyrethroid resistance in An. gambiae in Africa [76].…”
Section: Discussionmentioning
confidence: 70%
“…Our data resource includes CNVs at four Cyp gene loci (Cyp6p/aa, Cyp6m, Cyp6z, and Cyp9k), which could serve as molecular markers of CYP-mediated metabolic resistance. Glutathione Stransferase enzymes are also associated with metabolic resistance to pyrethroids (Ochieng'Opondo et al 2016;Adolfi et al 2019) B A Figure 5. Nucleotide diversity within the female-specific exon 5 of the doublesex gene (dsx; AGAP004050), a key component of the sex determination pathway and a gene targeted for Cas9-based homing endonuclease gene drive (Kyrou et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In both plots, the location of exon 5 within the femalespecific isoform (AGAP004050-RB; AgamP4.12 gene set) is shown above (black indicates coding sequence; gray, untranslated region), with additional annotations above to show the location of Cas9 target sequences containing at most one SNP, and the putative exon splice enhancing sequences ("RE") reported by Scali et al (2005). as well as other insecticide classes (Mitchell et al 2014;Riveron et al 2014;Pavlidi et al 2018;Adolfi et al 2019), and we found CNVs at the Gste locus that could serve as molecular markers of this alternative resistance mechanism, which is not inhibited by PBO. Gste CNVs were less prevalent in our data set than Cyp CNVs, and the geographical distribution also differed, suggesting they may be driven by different selection pressures (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations